Blood test findings in a large cohort of Olympic athletes: a cross-sectional study - Ferrera, A.; Di Gioia, G.; Spinelli, A.; Fiore, R.; Zampaglione, D.; Serdoz, A.; Squeo, M. R. (Journal of Science and Medicine in Sport, 2025)
Objectives Olympic athletes are often considered the pinnacle of health and performance. However, routine blood tests may reveal biochemical abnormalities. Understanding these abnormalities is crucial for optimizing athlete health and performance.